Kvartærgeologisk kartlegging og isavsmeltingshistorie i Sunndalen, Møre og Romsdal - Østergaard, Celine Djuve (The University of Bergen, 2013)
The age of three terminal glacial deposits located at Hoås, Gikling and Romfo in the Sunndalen valley, Møre & Romsdal, has been uncertain. The aim of this study has been to document these deposits to clarify the chronology and to reconstruct the deglaciation history of the area. The methods used in this study are quaternary mapping and examination of the sedimentary stratigraphy. Ground Penetrating Radar measurements were also conducted. Correlation to established sea level curve diagrams has been used for an indirect dating of the deposits. Theoretical glacier surface profiles have been developed to connect the terminal deposits to lateral moraines in the study area. These have been used to reconstruct the simultaneous glacier extent of the glacier in Sunndalen. The dating methods shows that the age of the deposits at Hoås and Gikling is respectively from early Younger Dryas and late Younger Dryas (12 800-11 600 yr BP). Romfo is situated above the marine limit of the valley, and it is therefore still uncertain if this deposit also is of a late Younger Dryas age, or is slightly younger. The glacial extent is reconstructed for four stages of readvance or stagnation during the deglaciation phase, from the oldest to the youngest; Løstøltrinnet, Hoåstrinnet - early Younger Dryas, Giklingtrinnet - late Younger Dryas and Romfotrinnet. Even though each of these stages and the terminal deposits at Hoås and Gikling most likely represents glacial readvances and periods of stagnation, the results unambiguously shows that a net deglaciation has occurred trough the period Younger Dryas. This deglaciation chronology can be connected to a somewhat similar deglaciation history in the Trondheimsfjorden area, but differs from the development in the South Western parts of Norway, where at the same time the glacier reached its maximum extent at the end of this cold period. Alderen på tre randavsetningar lokalisert ved Hoås, Gikling og Romfo i Sunndalen, Møre og Romsdal, har vore uviss. Målsettinga med denne studien var å ...